TRUST-IN-SUPERVISOR: ANTECEDENTS AND EFFECT ON AFFECTIVE ORGANIZATIONAL COMMITMENT - June M. L. Poon; Mohd Radzuan Rahid; Abdullah Sanusi Othman (Asian Academy of Management Journal, 2006)
This study tested a model of trust-in-supervisor that included propensity to trust and supervisor attributes (i.e., ability, benevolence, and integrity) as antecedents and affective organizational commitment and helping intention as criterion outcomes. A field survey using a structured questionnaire was used to gather data from 155 white-collar employees from diverse occupations and organizations. Path analysis results showed that supervisor ability, benevolence, and integrity as well as employees' propensity to trust were positively associated with trust-in-supervisor. Trust-in-supervisor, in turn, predicted employees' affective organizational commitment but did not have any influence on their willingness to help co-workers. Implications of the findings and suggestions for future research are discussed.